Discrepancy of terminology in BPM-system implementation - Abdullah, Shima (IADIS press, 2010)
Organizations worldwide are investing in BPM-systems and are becoming more prevalent in an attempt to gain better competitive advantage. Despite immense attention in BPM-systems implementation, it has introduced a new problem where terms to describe the implementation phases and activities are inconsistent and cause confusion for practitioners as well as research academics. This study investigates this confusion in terminology by reviewing current literature. First it introduces the concepts and definitions of BPM and BPM systems. It then investigates system implementation categorization and highlights the conflicting terminology. This is an on-going review of literature and this paper makes an interim report of findings.